2014
DOI: 10.1038/srep06602
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual variation in core microbiota in peri-implantitis and periodontitis

Abstract: The oral microbiota change dramatically with each part of the oral cavity, even within the same mouth. Nevertheless, the microbiota associated with peri-implantitis and periodontitis have been considered the same. To improve our knowledge of the different communities of complex oral microbiota, we compared the microbial features between peri-implantitis and periodontitis in 20 patients with both diseases. Although the clinical symptoms of peri-implantitis were similar to those of periodontitis, the core microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
149
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(177 citation statements)
references
References 55 publications
21
149
2
5
Order By: Relevance
“…However, several recent studies reported that the microbial composition of biofilm was more complex in peri-implant disease than in periodontal disease. The prevalence of periodontopathic bacteria is not high in peri-implantitis (26,27,46,47). Future studies may help to clarify these findings.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, several recent studies reported that the microbial composition of biofilm was more complex in peri-implant disease than in periodontal disease. The prevalence of periodontopathic bacteria is not high in peri-implantitis (26,27,46,47). Future studies may help to clarify these findings.…”
Section: Discussionmentioning
confidence: 93%
“…These findings highlight the importance of periodontal treatment of residual dentition before placement of osseointegrated dental implants (14,25). However, a recent hypothesis holds that the core microbiota in peri-implantitis and periodontitis exhibits intraindividual variation (26,27).…”
Section: Introductionmentioning
confidence: 87%
“…Casado et al (2013) realizaron un estudio en el cual incluyeron 215 pacientes con edentulismo parcial y que contaban con implantes osteointegrados, evaluaron el riesgo de desarrollar periimplantitis relacionada a la presencia de periodontitis crónica, obteniendo como resultado que aquellos pacientes con enfermedad periodontal crónica tenían 4 veces mayor riesgo de desarrollar periimplantitis. Maruyama et al (2014) reportaron que la periimplantitis se desarrollaba a partir de microorganismos provenientes de los órganos dentarios remanentes, sin embargo los microorganismos varían en un mismo órgano dentario y en el implante del mismo individuo, esto es debido a la presencia de ligamento periodontal y de la vascularidad en el periodonto. Dentro de los principales microorganismos relacionados a la periimplantitis se encuentran el Aggregatibacter actinomycetemcomitans, Porphyromona gingivalis, Treponema denticola, Tannerella forsythia y la Prevotella interme- dia si bien estos se encuentran tanto en periodonto sano como en periodontopatias, la presencia que se observa de estos microorganismos es más elevada en la periimplantitis, esto de acuerdo a Ata- .…”
Section: Introduccionunclassified
“…Their proportions are often highly elevated within diseased periodontal sites, and clinical studies have consistently associated them with various forms of periodontal disease, especially chronic periodontitis (7)(8)(9)(10)(11)(12). High levels of treponeme taxa are also frequently detected within endodontic infections and oral-implant infections (e.g., peri-implantitis) (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%